Minnelide Inhibits Androgen Dependent, Castration Resistant Prostate Cancer Growth by Decreasing Expression of Androgen Receptor Full Length and Splice Variants. Issue 6 (1st February 2017) - Isharwal, Sumit; Modi, Shrey; Arora, Nivedita; Uhlrich, Charles; Giri, Bhuwan; Barlass, Usman; Soubra, Ayman; Chugh, Rohit; Dehm, Scott M.; Dudeja, Vikas; Saluja, Ashok; Banerjee, Sulagna; et al.
Abstract : BACKGROUND: With almost 30, 000 deaths per year, prostate cancer is the second‐leading cause of cancer‐related death in men. Androgen Deprivation Therapy (ADT) has been the corner stone of prostate cancer treatment for decades. However, despite an initial response of prostate cancer to ADT, this eventually fails and the tumors recur, resulting in Castration Resistant Prostate Cancer (CRPC). Triptolide, a diterpene triepoxide, has been tested for its anti‐tumor properties in a number of cancers for over a decade. Owing to its poor solubility in aqueous medium, its clinical application had been limited. To circumvent this problem, we have synthesized a water‐soluble pro‐drug of triptolide, Minnelide, that is currently being evaluated in a Phase 1 clinical trial against gastrointestinal tumors. In the current study, we assessed the therapeutic potential of Minnelide and its active compound triptolide against androgen dependent prostate cancer both in vitro as well as in vivo. METHODS: Cell viability was measured by a MTT based assay after treating prostate cancer cells with multiple doses of triptolide. Apoptotic cell death was measured using a caspase 3/7 activity. Androgen Receptor (AR) promoter‐binding activity was evaluated by using luciferase reporter assay. For evaluating the effect in vivo, 22Rv1 cells were implanted subcutaneously in animals, following which, treatment was started with 0.21 mg/kg Minnelide. RESULTS: Our study showed that treatment with triptolide induced apoptotic cell death in CRPC cells. Triptolide treatment inhibited AR transcriptional activity and decreased the expression of AR and its splice variants both at the mRNA and the protein level. Our studies show that triptolide inhibits nuclear translocation of Sp1, resulting in its decreased transcriptional activity leading to downregulation of AR and its splice variants in prostate cancer cells. In vivo, Minnelide (0.21 mg/kg) regressed subcutaneous tumors derived from CRPC 22RV1 at our study endpoint. Our animal studies further confirmed that Minnelide was more efficacious than the standard of care therapies, Docetaxel and Enzalutamide. CONCLUSION: Our study indicates that Minnelide is very effective as a therapeutic option against CRPC at a dose that is currently tolerated by patients in the ongoing clinical trials. Prostate 77: 584–596, 2017 . © 2017 Wiley Periodicals, Inc.